Study of poly(3,4-ethylenedioxythiophene) based counter electrodes for efficient dye-sensitized solar cell - Mustafa, Muhammad Norhaffis (2017)
In this work the enhancement of dye-sensitized solar cell (DSSC) performance was studied by developments of new counter electrode (CE) using a combination of three different materials namely poly(3,4-ethylenedioxythiophene) (PEDOT), carbon-based material (CBM; graphene oxide (GO), reduced graphene oxide (rGO), nanocrystalline cellulose (NCC) and multi-walled carbon nanotube (MWCNT)) and titanium dioxide (TiO2). The counter electrode was prepared by coating indium tin oxide (ITO) glass with TiO2 followed by deposition of PEDOT incorporated with different CBMs to produce novel CEs with high performance. Among the CEs PEDOT-NCC/TiO2 exhibited the highest PCE of 2.10 % compared to PEDOT-MWCNT/TiO2 (1.29 %), PEDOT-rGO/TiO2 (1.10 %) and PEDOT-GO (1.17 %). PEDOT-NCC/TiO2 also displayed a lower charge transfer resistance (Rct = 2.4 Ω) and higher cathodic peak current density (Icp = -2.60 mA.cm-2) compared to other CEs due to the synergistic effect of high conductivity of PEDOT, high surface area and high optical transparency of NCC and porous structure of TiO2 that provide large surface area. The impact of this study in photovoltaic technology is to produce an efficient and low cost CE that capable to substitute a typical CE in DSSC which is platinum that is expensive and rare metal. The future plan can be pursued by producing a flexible CE to increase its application in various fields.